Sclerosing angiomatoid nodular transformation of the spleen: case report of a metastatic carcinoma-simulating disorder - Pinheiro, João L (J Surg Case Rep, 2019)
Sclerosing angiomatoid nodular transformation (SANT) is a rare nonneoplastic splenic disorder of unknown etiopathogenesis. This condition is usually found incidentally on imaging studies. Because of its similar features, SANT can wrongly be described as metastatic carcinoma. A 61-year-old Caucasian male was referred to our general surgery outpatient clinic regarding unusual splenic nodular formations in a routine abdominal ultrasound. All diagnostic exams performed confirmed metastatic splenic lesions, but no primary tumor was found. A laparoscopic splenectomy was performed for diagnostic purposes. Histopathology revealed SANT. Benign tumors of the spleen are uncommon entities and can easily be mistaken by malignant secondary lesions. The differential diagnosis of SANT should include other vascular lesions as well as metastatic carcinoma and inflammatory pseudotumor. It is widely recommended that a splenectomy should be performed because only by histopathology and immunohistochemistry staining, the definitive diagnosis of SANT can be made.